2022
DOI: 10.3389/fimmu.2022.954567
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis highlights three distinct immune profiles of high-risk oral epithelial dysplasia

Abstract: Oral potentially malignant disorders (OPMD) are precursors of oral squamous cell carcinoma (OSCC), and the presence of oral epithelial dysplasia (OED) in OPMD confers an increased risk of malignant transformation. Emerging evidence has indicated a role for the immune system in OPMD disease progression; however, the underlying immune mechanisms remain elusive. In this study, we used immune signatures established from cancer to delineate the immune profiles of moderate and severe OED, which are considered high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
4
7
0
Order By: Relevance
“…Gan et al . 40 has also shown similar finding of PELs using the RNA sequencing of the immune infiltrating sites within the moderate and severe OED. They have stated in their work that the lack of CD8 T-cells in non-cytotoxic subtype and non-immune reactive subtype can lead to progression in moderate and severe dysplasia.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Gan et al . 40 has also shown similar finding of PELs using the RNA sequencing of the immune infiltrating sites within the moderate and severe OED. They have stated in their work that the lack of CD8 T-cells in non-cytotoxic subtype and non-immune reactive subtype can lead to progression in moderate and severe dysplasia.…”
Section: Discussionsupporting
confidence: 56%
“…For progression free survival, we analysed the clinical, pathological, and nuclear features and found that apart from binary grading in OED, the variation in basal and epithelial layer NC to be associated with improved PFS while minimum number of in basal layer NC, epithelial layer NC and PEL to be associated with increased risk of malignant transformation or poor survival. Gan et al 40 has also shown similar finding of PELs using the RNA sequencing of the immune infiltrating sites within the moderate and severe OED. They have stated in their work that the lack of CD8 Tcells in non-cytotoxic subtype and non-immune reactive subtype can lead to progression in moderate and severe dysplasia.…”
Section: Survival Analysismentioning
confidence: 56%
See 1 more Smart Citation
“…2 To resist this cancer-promoting effect, the immune microenvironmental with immune surveillance features has been elucidated in OLK with epithelial dysplasia. 8,19 In this study, epithelial dysplasia occurred in all samples of OLK and OLK concomitant with OSF, but not observed in all OSF samples. Thus, immune cell infiltration in both OLK and OLK concomitant with OSF was higher than that in OSF.…”
Section: Pd-l1 and Ki-67 Expressionmentioning
confidence: 46%
“…Epithelial dysplasia is a common risk factor for malignant transformation of OLK 2 . To resist this cancer‐promoting effect, the immune microenvironmental with immune surveillance features has been elucidated in OLK with epithelial dysplasia 8,19 . In this study, epithelial dysplasia occurred in all samples of OLK and OLK concomitant with OSF, but not observed in all OSF samples.…”
Section: Discussionmentioning
confidence: 71%